Wide FOV metalens for near-infrared capsule endoscopy: advancing compact medical imaging - Moghaddasi Mojtaba; Perez Coca Erik Edilson; Ye Danni; Flores Diego Alejandro; Wu Xudong; Jalal Abdul; Ren Ziming; Abrinaei Fahimeh; Hu Bin (Nanophotonics)
This study presents the design, fabrication, and characterization of a wide field-of-view (FOV) metalens optimized for capsule endoscopy. The metalens achieved a 165° FOV with a high modulation transfer function (MTF) of 300 lines per millimeter (lp/mm) across the entire FOV, operating in the near-infrared (NIR) narrow-bandpass imaging at 940 nm. The performance of the metalens-based system is evaluated using two bandwidths, 12 nm and 32 nm, showing MTF values of 0.2 and 0.3 at 250 lp/mm, respectively. The metalens-based system maintains a compact form factor with a total track length of 1.4 mm and a diameter of 1.58 mm. Compared to a traditional 108° FOV endoscope, the nano-optic capsule endoscope demonstrated superior performance in terms of FOV, contrast, and resolution. This advancement represents a significant step toward enhancing diagnostic capabilities in medical imaging, offering improved performance in a more compact package compared to conventional optics.